The Effect of The Belief System, Family Organizations and Family Communication on Covid-19 Prevention Behavior: The Perspective of Family Resilience - Fadmawaty, Ani; Wasludin, Wasludin (TDMRC, Universitas Syiah Kuala, 2021)
Family resilience plays an important role, especially in dealing with prolonged problems or crises such as the COVID-19 pandemic. The absence of family resilience might result in family breakdown, decreased family function in decision making, and destroy values in family life. This study aims to determine the effect of belief systems, organizational patterns, and family communication on COVID-19 prevention behavior within the framework of family resilience. The study focuses on factors that most likely influence COVID-19 prevention behavior. This research is a descriptive-analytic study using a cross-sectional approach. A total of 100 respondents representing households in the Banten province filled out an online questionnaire using Google Form. In this study, the multivariate analysis used is multiple logistic regression. The analysis showed that the variables that had significant relationships with COVID-19 prevention behavior were the belief system (p = 0.005), family organization (p = 0.008), and family communication (p = 0.001). The results of this study also show that family communication is the most related variable with an odds ratio of 2694, which means that family communication has the greatest influence of 2-3 times of ?? in efforts to prevent COVID-19.